Empire and the social sciences global histories of knowledge - Adelman, Jeremy (Bloomsbury Academic, 2019)
"This thought-provoking and original collection looks at how intellectuals and their disciplines have been shaped, halted and advanced by the rise and fall of empires. It illuminates how ideas did not just reflect but also moulded global order and disorder by informing public policies and discourse. Ranging from early modern European empires to debates about recent American hegemony, Empire and the Social Sciences shows that world history cannot be separated from the empires that made it, and reveals the many ways in which social scientists constructed empires as we know them. Taking a truly global approach from China and Japan to modern America, the contributors collectively tackle a long durée of the modern world from the Enlightenment to the present day. Linking together specific moments of world history it also puts global history at the center of a debate about globalization of the social sciences. It thus crosses and integrates several disciplines and offers graduate students, scholars and faculty an approach that intersects fields, crosses regions and maps a history of global social sciences."--Bloomsbury Publishing